2005
DOI: 10.2214/ajr.184.2.01840511
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI Features of Pure Acinar Cell Carcinoma of the Pancreas in Adults

Abstract: Pure acinar cell carcinoma of the pancreas is usually an exophytic, oval or round, well-marginated, and hypovascular mass on CT and MRI. It typically is completely solid when small and contains cystic areas due to necrosis when large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 19 publications
5
99
2
3
Order By: Relevance
“…The preoperative imaging of ACC is generally nonspecific, although few radiologic patterns have been described. Tatli et al reported that ACCs are well-marginated hypovascular lesions at both computed tomography (CT) and magnetic resonance imaging (MRI) with cystic areas in 55% of cases [15]. Chiou et al described ACCs as hypodense masses at CT with welldefined enhancing capsule [16]; occasionally, intratumoral calcification and necrosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The preoperative imaging of ACC is generally nonspecific, although few radiologic patterns have been described. Tatli et al reported that ACCs are well-marginated hypovascular lesions at both computed tomography (CT) and magnetic resonance imaging (MRI) with cystic areas in 55% of cases [15]. Chiou et al described ACCs as hypodense masses at CT with welldefined enhancing capsule [16]; occasionally, intratumoral calcification and necrosis have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor may be associated with elevated serum concentrations of tumor markers, in particular CA19-9 or carcinoembryonic antigen; increased AFP levels have been described in individual cases [12]. Imaging typically reveals an exophytic, oval or round hypovascular mass [13]. Diagnosis is confirmed by biopsy on surgical exploration or – as in this case – by endoscopic ultrasound-guided fine-needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Thick-walled pseudocysts may resemble an acinar cell carcinoma, but a clinical history of pancreatitis is almost always present [ 60 ].…”
Section: Acinar Cell Carcinomamentioning
confidence: 99%